My foots in the stirrup-- my pony won't stand - Bly, Stephen A., 1944-2011 (Bly, Stephen A., 1944-2011. Code of the West, 1996)
Tap and Pepper Andrews want to settle down, raise some cattle, and start a family. But no matter where they go, the past is already there ahead of the ex-convict and his former dance-hall girl.